Comparison of virtual machines using different virtualization technologies on linux platform / Mohd Khairil Mohd Appandi - Mohd Khairil, Mohd Appandi (Faculty of Information Technology and Quantitative Sciences, 2006)
In computing, virtualization involves the process of presenting computing resources whereby users and applications can easily get value out of them, rather than presenting them in a way dictated by their implementation, geographic location, or physical packaging. In other words, it provides a logical rather than physical view of data, computing power, storage capacity, and other resources. Basically, this research project is concerned with comparison of two virtual machines using two different virtualization technologies (VMware and Parallels) that run on the same Linuxplatform (Fedora Core 4) in a single personal computer (PC) in order to show the performance respectively. It uses the host-guest virtualization approach whereby Windows XP Professional acted as a host operating system while both virtualmachines appears to be guest operating systems (Fedora Core 4) respectively. In thiscase, it applies the VMware and Parallels virtualization technology that acted as “virtual machine monitors” (VMMs) or “hypervisors” to create such a greatenvironment in a single hardware platform (PC). As for the performance, the virtual machines are able to run multiple operating systems in a single hardware platform in order to reduce the cost of the real hardware and software. In addition to that, it uses a variety of virtualization techniques like simulation, emulation, and hardware or software partitioning of the resources. During the project development, there are fivemethodologies used in order to accomplish this research paper. They are started withthe information gathering, analysis, development, testing and implementation, and ended by the documentation.